Analysis of the Influence of Analytical Mechanics Concept on the Development of Modern Physics - Puspitasari, Ayunda; Mufida, Fathiyya; Setiaji, Bayu (Jurnal Pendidikan dan Ilmu Fisika, 2024)
Physics has undergone development over time, one of which is through modern physics that studies the behavior of matter and energy at the atomic and subatomic particle scale using the concept of analytical mechanics to explain phenomena on a microscopic scale. The purpose of this article is to investigate the influence of analytical mechanics on the advancement of modern physics using a qualitative literature review approach. The literature review involved gathering information related to the study of mechanics and modern physics. The analysis results indicate that analytical mechanics such as Lagrangian and Hamiltonian have influenced the progress of modern physics significantly. This analytical mechanics has made a substantial contribution to modern physics by providing strong theoretical concepts, aiding theoretical research, enabling the analysis of complex physical phenomena, and offering practical applications across various scientific fields. The conclusion drawn from this analysis is the significant theoretical impact of analytical mechanics on the development of modern physics.